Occultations by Small Non-spherical Trans-Neptunian Objects. I. A New Event Simulator for TAOS II. (22nd April 2019) - Castro-Chacón, J. H.; Reyes-Ruiz, M.; Lehner, M. J.; Zhang, Z.-W.; Alcock, C.; Guerrero, C. A.; Hernández-Valencia, B.; Hernández-Águila, J. B.; Nuñez, J. M.; Salinas-Luna, J.; Silva, J. S.; Alexandersen, M.; et al.
Abstract: We present a new occultation event simulator for the Trans-Neptunian Automated Occultation Survey (TAOS II). We have developed a method to compute occultation shadows by small objects with non-circular apparent shapes (as may result from an intrinsic morphology or from the projection of a contact binary). The new simulator calculates diffraction features in the occultation shadows, as well as resulting light curves as would be measured by the TAOS II survey system. We include effects such as the spectral type and finite angular size of the occulted star. We find that occultation events, especially by Trans-Neptunian Objects with diameters ∼3 km may be misidentified or mischaracterized when not taking non-spherical shapes into account.